A scaling relation for the molecular cloud lifetime in Milky Way-like galaxies - Jeffreson, Sarah; Keller, Benjamin W.; Winter, Andrew J.; Chevance, Mélanie; Kruijssen, Diederik; Krumholz, Mark R.; Fujimoto, Yusuke (Monthly notices of the Royal Astronomical Society, 2021)
We study the time evolution of molecular clouds across three Milky Way-like isolated disc galaxy simulations at a temporal resolution of 1 Myr and at a range of spatial resolutions spanning two orders of magnitude in spatial scale from similar to 10 pc up to similar to 1 kpc. The cloud evolution networks generated at the highest spatial resolution contain a cumulative total of similar to 80000 separate molecular clouds in different galactic-dynamical environments. We find that clouds undergo mergers at a rate proportional to the crossing time between their centroids, but that their physical properties are largely insensitive to these interactions. Below the gas-disc scale height, the cloud lifetime tau(life) obeys a scaling relation of the form tau(life)proportional to l(-0.3) with the cloud size l, consistent with over-densities that collapse, form stars, and are dispersed by stellar feedback. Above the disc scale height, these self-gravitating regions are no longer resolved, so the scaling relation flattens to a constant value of similar to 13 Myr, consistent with the turbulent crossing time of the gas disc, as observed in nearby disc galaxies.
Gesehen am 08.09.2021